Cytokines and Hormones That Contribute to the Positive Association between Fat and Bone - Naot, Dorit; Cornish, Jillian (Frontiers in Endocrinology, 2014)
The positive association between body weight and bone density has been established in numerous laboratory and clinical studies. Apart from the direct effect of soft tissue mass on bone through skeletal loading, a number of cytokines and hormones contribute to the positive association between adipose and bone tissue, acting either locally in sites where cells of the two tissues are adjacent to each other or systemically through the circulation. The current review describes the effects of such local and systemic factors on bone physiology. One class of factors are the adipocyte-secreted peptides (adipokines), which affect bone turnover through a combination of direct effects in bone cells and indirect mechanisms mediated by the central nervous system. Another source of hormones that contribute to the coupling between fat and bone tissue are beta cells of the pancreas. Insulin, amylin and preptin are co-secreted from pancreatic beta cells in response to increased glucose levels after feeding, and are also found in high circulating levels in obesity. A number of peptide hormones secreted from the gastrointestinal tract in response to feeding affect both fat and bone cells and thus can also act as mediators of the association between the two tissues. The current review focuses on results of laboratory studies investigating possible mechanism involved in the positive association between fat mass and bone mass.